Influencia del cultivo de maíz (Zea mays) en la calidad del suelo en el sitio Los Amarillos, Cantón Tosagua. - Daza López, Gustavo Patricio (2018)
The research aimed to evaluate the influence of maize (Zea mays) in soil quality on site Yellows, Canton Tosagua. It ran from April 2015 as experimental research. It began with the analysis phase of production activities conducting a survey to corn growers site to determine the sequence of production activities carried out during the crop cycle before, during and after harvest, and identify processes thereof. In the phase of determination of soil quality three batches of greater extension were selected, in which three samples of each were taken and homogenized, obtaining an aliquot of each batch two times before planting and at the end harvest, the same as were transferred to the laboratory of soil, plant tissues and waters Pichilingue Tropical Experimental Station INIAP. cultivated areas were identified by the survey of producers site land preparation was established, variety used in planting, method for seeding and reseeding, weed control, number and shape of fertilization, and harvesting as production activities carried corn crop in the area. Analyses performed at the stage of pre-harvest and harvest determine that the soil is poor in organic matter (1,7 %) and nitrogen (15 ppm), while potassium (1,12 meq/100ml), calcium (17,5 meq/100ml) and magnesium (7 meq/100ml) are elevated values, placing the soil in a pH range between slightly acidic and practically neutral (6,58). These indicators allowed to determine that the soil has a high quality (0.62) at the pre-harvest stage, while at the harvest stage the soil has a moderate quality (0.56), according to the scale of transformation of soil classes floor.